Prospects of increase of the state energy assurance by means of phytoenergy - Григорюк, І. П.; Калініченко, В. М.; Малинська, Л. В. (Scientific Progress & Innovations, 2012)
The article deals with the necessity of urgent search of new alternative sources and technologies of power production with the use of renewable resources. The perspective of the cultivation of plants which effectively accumulate sun energy in the process of photosynthesis for the increase of energy assurance of the country has been grounded. The availability of phytoenergy use in the context of stable ecologically and economically balanced state development has been analyzed. Much attention is paid to the importance of scientists’ concentration on selection of new plant varieties with a high activity of photosynthetic apparatus and ability to accumulate biomass of the appropriate quality regardless of nutrition conditions.